2017
DOI: 10.1155/2017/4673047
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Recognition and Social Support on European Health Professionals’ Occupational Stress: A Demands-Control-Social Support-Recognition Bayesian Network Model

Abstract: Healthcare professionals undergo high levels of occupational stress as a result of their working conditions. Thus, the aim of this study is to develop a model that focuses on healthcare professionals so as to analyze the influence that job demands, control, social support, and recognition have on the likelihood that a worker will experience stress. The data collected correspond to 2,211 healthcare workers from 35 countries, as reported in the sixth European Working Condition Survey (EWCS). The results obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 67 publications
(64 reference statements)
1
18
0
Order By: Relevance
“…The systematic review revealed that high demands at work, minimal control of working conditions, little support from colleagues and superiors, and a seriously compromised employee sense of righteousness cause stress-related problems [10], resulting in poor health and reduced working capacity [11]. A more recent study focusing on healthcare professionals reported similar results, but the researchers concluded that recognition was the most crucial factor in reducing work-related stress [12]. When individuals must deal with stressful situations without real opportunities to influence them, it can lead to persistent stress [13].…”
Section: Introductionmentioning
confidence: 98%
“…The systematic review revealed that high demands at work, minimal control of working conditions, little support from colleagues and superiors, and a seriously compromised employee sense of righteousness cause stress-related problems [10], resulting in poor health and reduced working capacity [11]. A more recent study focusing on healthcare professionals reported similar results, but the researchers concluded that recognition was the most crucial factor in reducing work-related stress [12]. When individuals must deal with stressful situations without real opportunities to influence them, it can lead to persistent stress [13].…”
Section: Introductionmentioning
confidence: 98%
“…We are poor at acknowledging our own weakness and need for help and have been conditioned to independence and self-sufficiency. We are very much control-oriented, and a high demand-low control environment is a major driver of psychological stress and physical illness [5]. COVID-19 is taking us to such a place and that puts surgeons at more risk.…”
Section: Promoting Wellnessmentioning
confidence: 99%
“…Recently, the number of Studies using Bayesian networks in safety context is rising as this method provides reliable inferences regarding safety issues [16][17][18][19][20][21][22][23]. This includes evaluating the severity of traffic collisions, analysing their causes and/or predicting the probability of fatal and serious injuries.…”
Section: Approachmentioning
confidence: 99%
“…Discrete Bayesian Networks (BN) are probabilistic graphical models to learn the joint probability distribution (JPD) of a multivariate problem involving multinomial variables (22). The model is based on a directed acyclic graph that expresses the direct/conditional dependencies/independencies between the variables and simplifies the learning of the JPD, based on the factorization associated to the independencies given by the directed acyclic graph, DAG (Equation 1), and the interpretability of the resulting model.…”
Section: Modelmentioning
confidence: 99%